2022
DOI: 10.1002/cam4.4643
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy shows benefit in selected stage I uterine sarcoma: A risk scoring system based on a population analysis

Abstract: Background:The potential therapeutic benefit of adjuvant radiotherapy for patients with stage I uterine sarcoma has not been clear. In this study, we aimed to develop a risk scoring model to select the subgroup of patients with stage I uterine sarcoma who might benefit from adjuvant radiotherapy. Methods: Patients with stage I uterine sarcoma from the Surveillance, Epidemiology, and End Results program from 2010 to 2014 were retrospectively included in this analysis. Cox proportional hazards models were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Adjuvant oncologic regimens vary broadly with little consensus on the benefits of the addition of adjuvant radiotherapy (RT) or chemotherapy to optimize oncologic outcome and the application of systemic therapy regimens for improvement of the diseasefree survival remains controversial [11][12][13][14]. The same debate is ongoing about postoperative radiotherapy: Prior studies showed a significant reduction in the risk of locoregional failure with superior 5-year local control (LC) rates of 87% and 5-year diseasespecific survival after adjuvant RT as well as superior overall survival (OS) rates for uterine carcinosarcoma [15][16][17][18][19]. Further, brachytherapy (BT) added therapeutic value to the treatment of uterine sarcoma as it allows for better sparing of the surrounding tissue while maintaining high doses with conformal applicators and improving LC efficiently for 5-year rates of up to 91% [20].…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant oncologic regimens vary broadly with little consensus on the benefits of the addition of adjuvant radiotherapy (RT) or chemotherapy to optimize oncologic outcome and the application of systemic therapy regimens for improvement of the diseasefree survival remains controversial [11][12][13][14]. The same debate is ongoing about postoperative radiotherapy: Prior studies showed a significant reduction in the risk of locoregional failure with superior 5-year local control (LC) rates of 87% and 5-year diseasespecific survival after adjuvant RT as well as superior overall survival (OS) rates for uterine carcinosarcoma [15][16][17][18][19]. Further, brachytherapy (BT) added therapeutic value to the treatment of uterine sarcoma as it allows for better sparing of the surrounding tissue while maintaining high doses with conformal applicators and improving LC efficiently for 5-year rates of up to 91% [20].…”
Section: Introductionmentioning
confidence: 99%